Sifat Anti Cendawan Trichophyton mentagrophytes dan Candida albicans dari Zat Ekstraktif Kayu Pelanjau (Pentaspadon motleyi) - Fathul Yusro; Wasrin Syafii; Eko Sugeng Pribadi (Fakultas Kehutanan Universitas Gadjah Mada, 2010)
Trichophyton mentagrophytes and Candida albicans Antifungal Activity of Palanjau (Pentaspadon metleyi) Wood ExtractivesPelanjau wood (P. motleyi) extractives traditionally used as medicine for skin infection such as scabies (tinea) and rash caused by fungal T. mentagrophytes and C. albicans. The aim of this research was to identify the effectiveness of pelanjau wood extractives on growth inhibitory of fungal T. mentagrophytes and C. albicans, isolate and identify extract compounds which have antifungal properties. Extraction and fractionation process yielded 7,04% of ethanol extract consisting of 0,28%, 1,28%, 1,19% and 4,29% of n-hexane, diethyl ether, ethyl acetate and residue fractions, respectively. Antifungal activity of pelanjau wood extract more effective on C. albicans growth inhibition than T. mentagrophytes fraction ethyl acetate at (0,03 and 0,06 mg/ml of MIC and MFC, respectively). Isolation of ethyl acetate fraction was resulted dominant compound EA6a and EA6c. NMR and GC MS analysis of compound EA6a indicate 2-Hidroxy octadecanoid acid, Hexadecanoic acid, Ethyl oleate, Octadecanoic acid, Vanilin and phenol,2-methoxy-4-(1-propenyl) as the possibly main component belonged to fatty acid and phenol group. Compound EA6c indicate Phenol, 4-(1,1 dimetylpropyl), Nonylphenol isomer, Phenol,4-(1,1,2,2-tetrametylbutyl), Nonyl-phenol mix isomer dan 4-Nonylphenol as the possibly main component in belong to phenol group.